HPLC-MS standardization and validation methods for determination of calactin content in dichloromethane fraction of Calotropis gigantea (L.) Dryand. (Niu jiao gua) stem bark and its application in prediction of anticancer activities - Naphat Kaewpaeng; Sudaporn Wongwan; Khemmachat Pansooksan; Chanakan Chailom; Pattaraporn Chaisupasakul; Dumrongsak Pekthong; Nitra Nuengchamnong; Zhi-Hong Jiang; Li-Ping Bai; Piyarat Srisawang; Supawadee Parhira (Heliyon)
Calactin, a doubly-linked cardenolide, is commonly found in Apocynaceae family including Calotropis gigantea (L.) Dryand. (Niu jiao gua, C. gigantea). This phytochemical has gained recognition for its potential as an anticancer agent and a marker for anticancer properties. Our previous reports demonstrated the remarkable anti-liver and anti-colon cancer activities both in vitro and in vivo of the dichloromethane fraction from the stem barks of C. gigantea (CGD). However, quantitative analysis of calactin content in CGD by using a high-performance liquid chromatography (HPLC) – ultraviolet (UV) method was limited. Therefore, this study aimed to develop more sensitive and reliable method for measurement of calactin in CGD by using a HPLC- electrospray ionization mass spectrometry (ESI-MS) for its application on quality control and prediction of anticancer activity of CGD. The study utilized a HPLC-ESI-MS system, negative mode, for standardization and validation. An octadecylsilane column and a mixture of acetonitrile and water containing 0.1 % formic acid in gradient system were used as a stationary phase and a mobile phase, respectively. The method was validated in terms of linearity, accuracy, precision, recovery, limit of detection (LOD), and limit of quantitation (LOQ). The linearity of the developed technique was verified within the calactin concentrations range from 1 to 50 μg/mL, exhibiting a linear coefficient of determination (R2) greater than 0.998. The LOD and LOQ were 0.1 and 1 μg/mL, respectively. The proposed methodology met the acceptance criteria according to the International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use (ICH) guideline Q2(R1). Therefore, the method was suitable for the quality control of CGD. Additionally, we suggest applying the established protocol to quantify the calactin contents in CGDs collected over a period of one year (12 months) to investigate the correlation to their cytotoxicities against human cell lines derived from colon cancer (HCT116), human hepatoblastoma (HepG2) and human cell line derived from stomach cancer metastasized to liver (MKN74). This will help in predicting its cytotoxicity against HCT116, HepG2 and MKN74. In summary, the established HPLC-ESI-MS method is suitable for both quality control and predicting of CGD anticancer activities for further utilization.